Professionalisation and Professionalism: Diphtheria and Medical Practice in Minnesota 1850–1910. (31st December 2019) - Rushton, Alan R
Summary: The evolution of professionalism in Minnesota began when allopathic and homeopathic physician leaders organised medical societies and colleges to define and perpetuate their styles of practice. The epidemics of diphtheria that ravaged the state demanded prompt public health measures of quarantine to reduce the spread of the disease. Then the successful utilization of diphtheria antitoxin in Europe encouraged its local production in Minnesota and the re-education of all physicians there to convince them that they were no longer helpless to treat this infection that killed so many children. Their professionalisation was completed when they implemented the cure for diphtheria that laboratory science had produced. Homeopathic and allopathic practices converged as Minnesota physicians transformed their occupation from merely caring and comforting to actively treating and curing a serious infection.